2014
DOI: 10.1158/1078-0432.ccr-13-3230
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to Endocrine Treatments Is Associated with Tumor-Specific Molecular Changes in Patient-Derived Luminal Breast Cancer Xenografts

Abstract: Purpose: Patients with luminal breast cancer (LBC) often become endocrine resistant over time. We investigated the molecular changes associated with acquired hormonoresistances in patient-derived xenografts of LBC. Experimental Design: Two LBC xenografts (HBCx22 and HBCx34) were treated with different endocrine treatments (ET) to obtain xenografts with acquired resistances to tamoxifen (TamR) and ovariectomy (OvaR). PI3K pathway activation was analyzed by Western blot analysis and IHC and respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 48 publications
3
63
0
1
Order By: Relevance
“…We thus sought to assess the impact of modulating proliferation on the levels of EZH2 and H3K27me3 in the context of human breast cancers. We analyzed EZH2 and H3K27me3 levels by IHC in two previously characterized patient-derived xenografts (PDXs) of estrogen-positive breast cancer (Cottu et al 2014). The engrafted mice were treated with various combinations of endocrine therapies and the mTOR inhibitor everolimus, the impact of which on tumor proliferation was evaluated by Ki67 staining (Cottu et al 2014).…”
Section: H3k27me3 Homeostasis Is Compromised In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…We thus sought to assess the impact of modulating proliferation on the levels of EZH2 and H3K27me3 in the context of human breast cancers. We analyzed EZH2 and H3K27me3 levels by IHC in two previously characterized patient-derived xenografts (PDXs) of estrogen-positive breast cancer (Cottu et al 2014). The engrafted mice were treated with various combinations of endocrine therapies and the mTOR inhibitor everolimus, the impact of which on tumor proliferation was evaluated by Ki67 staining (Cottu et al 2014).…”
Section: H3k27me3 Homeostasis Is Compromised In Breast Cancermentioning
confidence: 99%
“…The engrafted mice were treated with various combinations of endocrine therapies and the mTOR inhibitor everolimus, the impact of which on tumor proliferation was evaluated by Ki67 staining (Cottu et al 2014). As previously reported (Supplemental Table S1; Cottu et al 2014), some drug combinations led to a near complete inhibition of cell proliferation (e.g., everolimus + fulvestrant), while other treatments only reduced proliferation (e.g., everolimus alone or everolimus + tamoxifen) or failed to impair proliferation (e.g., ovariectomy). Quantification of EZH2 signal revealed that it was highly correlated to Ki67 ( Fig.…”
Section: H3k27me3 Homeostasis Is Compromised In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo efficacy studies were performed in 8-to 12-week-old female Swiss nude mice implanted with the PDX HBCx22OvaR, as previously described (22), in accordance with the French Ethical Committee. First, a pharmacodynamic study was performed for 4 days to assess biomarker changes with samples removed 2 and 4 hours after treatment.…”
Section: Human Tumor Xenograftsmentioning
confidence: 99%
“…Finally, we analyzed the gene expression profiles of tamoxifen-resistant breast tumors established from primary ER␣-positive breast tumors in an in vivo tamoxifen treatment model (26). Among five replicates, the three tamoxifen-resistant breast tumors (m27, m58, and m69) showed slightly increased expression of IL6 and decreased expression of FOXA1 and ER␣ as compared with control ER␣-positive tumors (Fig.…”
Section: Increased Sphere-forming Activity In Tam-r Cellsmentioning
confidence: 99%